TFN Brownies by Suji / Nur Azila Umairah Mohd Ramli and Nur Suhaila Noorfaizan - Mohd Ramli, Nur Azila Umairah; Noorfaizan, Nur Suhaila (2022)
TFN Brownies or known as The Famous Nisha started their own business in 2016. TFN Brownies are famous with their own thin and crunchy brownies. They started this business with 3 product line which is walnut, chocolate chip and mint. Their mission is to be one of the best manufacturers that eager to be creative and take a good responsibility in quality of the product. Right now, there are 6 flavours that come up along the way till 2022 which is red velvet, mocha, and dark chocolate. The area of price is quite affordable and most customer can afford to buy it. The packaging of TFN Brownies also very user-friendly as they use a zip lock packaging so that the brownies will not sluggish, and it will give best satisfaction to a customer. This social media portfolio is to ensure the readers know about the organization activities like how to run and promoting their business which is TFNBrowniesbysuji. On these Facebook, readers will be exposed to business purposed about teaser, soft sell and hard sell which is for attracting consumers. This also is one way to keep the retaining customers and sustain the profit of organizations. Each of organization have their vision and mission to have a successful business. Our business also registered under SSM and go-e commerce. This is to ensure customers will have a trust to our company. TFNBrowniesbysuji that based on Rembau, Negeri Sembilan providing a good quality product. We provide few of ways of to get the product by COD and postage delivery. Every process of delivering to customers were done by our organization. Keeping up to date to customers to get the outcomes and it is one of the ways we stay connected with our customers. The goal of TFN Brownies' marketing strategy is to increase customer attraction by lowering prices while maintaining product quality. We provide a lower pricing because we believe that this will enable everyone to purchase the product. We also provide unique prices for our customers to purchase on specific days. All of business should have a social media to promote their product or services. TFN Brownies consisting of supply chain of organization which is supplier, stockist, agents, and dropship plays an important role in promoting and selling the products to get a revenue. Additionally, drop shippers are recognised as agents, whose only duties are to market things and make money. Social media such as Facebook page, help many small businesses to sell and publish about their products. TFNBrowniebysuji use a Facebook page to gain new customers and sustain remaining customer by posting hard sell and soft sell. Customers get their product from the link that has been posted in every posts.